Ask Singapore Homework?
Upload a photo of a Singapore homework and someone will email you the solution for free.
Question

One Answer Below
Anyone can contribute an answer, even nontutors.
Please explain, i don't understand the rounded part!! :' (
(x+2)² is equal to x² + 4x + 4,
not x² + 4
(x+2)² = 2x + 7
=> x² + 4x + 4 = 2x + 7
=> x² + 2x  3 = 0
=> (x+3)(x1) = 0
=> (x+3) = 0 or (x1) = 0
=> x = 3 or x =1
so, ur steps are incorrect,
but ur ans happens to b correct, by chance.
bcos ur step:
x²  2x  3 = 0
shld b (x3)(x+1) = 0,
not (x+3)(x1) = 0
See 1 Answer
I think you have expanded (x+2)^2 wrongly, hence you got x^2  2x 3 = 0 instead of x^2 + 2x  3 = 0.
I have also shown how you can simplify x^2 + 2x  3 to (x1)(x+3) in the grey box.